Legal Protection for Intellectual Property Holders in Business Activities in The Era of The Industrial Revolution 4.0 - Kurniawan, I Gede Agus; Aras Samsithawrati, Putu; Dharmawan, Ni Ketut Supasti (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2024)
The Industrial Revolution 4.0 brings new challenges in the protection of intellectual property rights (IPR) for business activities, such as the increased potential for IPR violations through massive digital dissemination, cross-border infringements, and the need for regulatory adjustments to accommodate the latest technological developments. Efforts to protect IPR in the digital era require more effective law enforcement, strong international cooperation, increased public awareness, and the availability of competent human resources in the field of IPR. The aim of this study is to analyze the legal protection for intellectual property rights holders in business activities during the Industrial Revolution 4.0 and to identify the challenges faced in these legal protection efforts. This research is normative legal research using a statute approach and a conceptual approach to examine primary, secondary, and tertiary legal materials related to the protection of intellectual property rights in business activities during the Industrial Revolution 4.0. Data collection techniques are carried out through literature studies and qualitative data analysis to understand legal concepts, identify problems, and find solutions in the legal protection of intellectual property rights holders. The results of the study show that the legal protection for intellectual property rights (IPR) holders in business activities during the Industrial Revolution 4.0 is regulated by various laws in Indonesia, such as the Copyright Law, Trademark Law, Patent Law, and Trade Secrets Law. Although there is already a legal framework, IPR protection in the digital era faces new challenges such as digital infringement, trade secret theft through illegal access, and online trademark and patent violations. The government has taken steps such as the enactment of the Information and Electronic Transactions Law (ITE Law), the establishment of the Directorate General of Intellectual Property (DJKI), and the signing of international agreements related to IPR. However, comprehensive efforts are needed from the government, businesses, and the public through regulatory improvements, law enforcement, socialization, IPR registration, information system security, monitoring, and international cooperation to effectively protect IPR. The main challenges include rapid technological development, cross-border violations, lack of public understanding, limited competent human resources, and still less effective law enforcement.